Effect of Normalizing Temperature on Microstructure, Texture and Magnetic Properties of Non-Oriented Silicon Steel - Changcheng Zhou; Shenteng Luan; Jialong Qiao; Haijun Wang (Metals)
In order to improve the magnetic properties of non-oriented silicon steel, the effects of different normalizing temperatures on the microstructure, texture, and magnetic properties of 3.0%Si 0.8%Al non-oriented silicon steel were studied by OM, EBSD, and a magnetic measuring instrument. The results show that the microstructure of the hot-rolled plate is obviously different along the thickness direction. Strong Goss texture and {001} ~ {112} texture are the main textures in the hot-rolled plate. After normalizing at 900 °C, 940 °C, and 980 °C and annealing at 940 °C, respectively, the average grain size of the normalized plates and the annealed sheets increases with the increase in the normalizing temperature, and the texture types of the normalized plates basically inherit that of the hot-rolled plates. With the increase in normalizing temperature, the intensity of the γ-fiber texture decreases, and the main texture types in the finished plates are {100} <012> texture and {111} <112> texture. The area fraction of {100} <012> texture in the finished sheet normalized at 980 °C and annealed is the largest, which is 20.3%, and the area fraction of {114} <481> texture is larger, which is 15.2%. The magnetic induction B50 of the finished sheets increases gradually with the increase in the normalizing temperature, from 1.662 T to 1.720 T; the low-frequency iron loss P1.5/50 decreased slightly from 2.46 W·kg−1 to 2.30 W·kg−1. The high-frequency iron loss P1.0/400 decreased significantly from 17.40 W·kg−1 to 15.75 W·kg−1. The results of the microstructure, texture, and magnetic properties show that the best normalizing temperature in this experiment is 980 °C.